2022
DOI: 10.1111/1751-2980.13137
|View full text |Cite
|
Sign up to set email alerts
|

Novel nomogram model for predicting 6‐week mortality in liver cirrhosis patients with acute upper gastrointestinal bleeding

Abstract: Objective To develop and validate a nomogram for predicting 6‐week mortality in patients with liver cirrhosis and acute upper gastrointestinal bleeding (UGIB) and to compare it with other commonly used scoring systems. Methods This retrospective study included cirrhotic patients with acute UGIB hospitalized between January 2013 and December 2020. Random sampling was used to divide patients into the training (n = 676) and validation cohorts (n = 291) at a 7:3 ratio. Multivariate logistic stepwise regression was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…According to predictive models for prognosis, systemic reviews of clinical data revealed that six independent risk factors (TB, INR, age, neutrophil count, HE level and urea level) appeared to be promising candidates for predicting poor prognosis, and multiple simpli ed prognostic scores were further developed for patients with HBV-ACLF [22][23][24]. In addition, upper gastrointestinal hemorrhage was also identi ed as an independent prognostic predictor for 6-week mortality in patients with liver cirrhosis [29]. However, there are no effective models for predicting disease prognosis in HBV-ACLF patients receiving arti cial liver therapy.…”
Section: Discussionmentioning
confidence: 99%
“…According to predictive models for prognosis, systemic reviews of clinical data revealed that six independent risk factors (TB, INR, age, neutrophil count, HE level and urea level) appeared to be promising candidates for predicting poor prognosis, and multiple simpli ed prognostic scores were further developed for patients with HBV-ACLF [22][23][24]. In addition, upper gastrointestinal hemorrhage was also identi ed as an independent prognostic predictor for 6-week mortality in patients with liver cirrhosis [29]. However, there are no effective models for predicting disease prognosis in HBV-ACLF patients receiving arti cial liver therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of UGIB in patients with liver cirrhosis, acute peripheral circulatory failure may suddenly occur, resulting in decreased blood perfusion in liver tissues, often accompanied by clinical manifestations such as blood volume decline, melena, and haematemesis. This disease progresses rapidly, with a mortality rate of Effects of gastrointestinal endoscopy at different time points on diagnosis and treatment of upper gastrointestinal bleeding in patients with liver cirrhosis above 10% if not treated promptly [4]. It is mentioned in Expert Consensus on Emergency Diagnosis and Treatment Procedures for Acute Upper Gastrointestinal Bleeding that gastrointestinal endoscopy is an effective means of diagnosis and treatment of UGIB upon liver cirrhosis [5].…”
Section: Introductionmentioning
confidence: 99%